Profil fitokimia dan aktivitas antibakteri fraksi etil asetat akar jarak pagar (Jatropha curcas Linn.) - Sudarman Rahman; Stevin Carolius Angga; Erwin Prasetya Toepak; Muhammad Takdir Bachtiar (Universitas Mataram, 2021)
Bacterial infections are a major cause of chronic infections and mortality that continues to threaten public health worldwide. Various medicinal plants used in folk medicine have demonstrated wound healing and antibacterial properties. The aims of the study are investigation phytochemical and antibacterial activity of ethyl acetate fraction from jarak pagar roots (Jatropha curcas Linn.). The roots were treated with maceration method using ethanol 70% and subsequently fractioned to ethyl acetate fraction. The fractions were used for phytochemical screening and antibacterial assay using Kirby and Bauer agar difussion method. The results showed that ethyl acetate fraction jarak pagar roots contained alkaloid, flavonoids, saponins, steroids, poliphenol dan tannins. The antibacterial activity of jarak pagar roots againts Staphylococcus aureus and Escherichia coli shows that the activity of this fraction with concentration 8 mg/mL has strong inhibitory potency against the growth S. aureus with inhibitory zone is 14,3 mm and has moderate inhibitory potency against E. coli with inhibitory zone is 9 mm. The increase concentrations of ethyl asetate fraction jarak pagar roots shows high inhibition diameter of bacterial growth.